Non-invasive Ultrasound Doppler Effect Based Method of Liquid Flow Velocity Estimation in Pipe - BIERNACKI, Pawel; GMYREK, Stanislaw; MAGIERA, Wladyslaw (Archives of Acoustics, 2023)
This paper discusses the estimation of flow velocity from a multi-sensor scenario. Different estimation methods were used, which allow the effective measurement of the actual Doppler shift in a noisy environment, such as water with air bubbles, and on this basis the estimation of the flow velocity in the pipe was calculated. Information fusion is proposed for the estimates collected. The proposed approach focuses on the density of the fluid. The proposed method is capable of determining the flow velocity with high accuracy and small variations. Simulation results for plastic and steel (both galvanized and non-galvanized) pipes show the possibility of accurate fluid flow measurements without the need for sensors inside the pipe.